Dysphagia in Rett Syndrome: A Descriptive Study - Mezzedimi, Chiara; Livi, Walter; De Felice, Claudio; Cocca, Serena (Annals of otology, rhinology & laryngology, 2017)
Rett syndrome (RS) is a neurodevelopmental disorder and the second major cause of mental retardation in females. The aim of this study was to evaluate swallowing problems of RS patients by endoscopic assessment and compile a list of suggestions for managing feeding and preventing complications. The sample consisted of 61 female patients (mean age = 13.6 years, range, 2-33 years) admitted to the Department of Neuropsychiatry, where they had previously been diagnosed with RS. Speech evaluation associated with observation during mealtimes was useful to formulate suggestions for caregivers. Progressive deterioration of feeding was commonly noted by caregivers. Fifty-four patients had a history of recurrent episodes of bronchitis. Oral apraxia, dyskinetic tongue movements, prolonged oral stage, and poor bolus formation were the most common findings in all patients. Dysphagia was primarily limited to oral preparatory phases, while the pharyngeal phase was normal in most patients. The high percentage of dysphagia suggests the need to accurately monitor the feeding capability of RS children. It is critical to correctly inform caregivers about safe swallowing procedures to reduce the incidence of fatal complications.